O sagrado e o profano do Saíré no distrito de Alter do Chão em Santarém – Pará e suas metamorfoses geográficas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The present work addresses crucial factors, such as the syncretism present in the district of Alter do Chão, integrated into the municipality of Santarém, in Pará. This syncretism refers to the fusion of elements of the Catholic church with indigenous elements. It is essential to explore the interpretations of the religious manifestation, especially the Sairé ritual, its characteristics, origins, history and changes over time, from the perspective of geographic science, including the analysis of the place and landscape. It is important to highlight that there are other similar cultural manifestations throughout Brazil. The objective of this study is to understand the dimension of the sacred and the profane in the Sairé festival in the district of Alter do Chão, Santarém, PA. The research was carried out through exploratory and explanatory fieldwork, allowing a chronological development. Bibliographical surveys on the sacred and profane, festivities, relationship with space, symbolism and cultural modifications were used. The research results reveal that the tradition of the Sairé rite occurred in other municipalities in the state of Pará, involving Alterrense families descended from the Borari indigenous people. This tradition has established itself as a constantly growing tourist attraction, concentrated in a single location. This work emphasizes that the spaces of representation, experience, sacred and profane are significant and highlights that the Sairé ritual is a living experience, not just a representation.
Keywords: Sincretismo; Sagrado-profano; Hierofania; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE